2019
DOI: 10.17239/l1esll-2019.19.01.13
|View full text |Cite
|
Sign up to set email alerts
|

The role of literature in the classroom: How and for what purposes do teachers in lower secondary school use literary texts?

Abstract: This study investigates the use of literary texts in 178 video-recorded LA lessons across 47 lower-secondary Norwegian classrooms. It offers a systematic overview of how literary texts are read, used, and discussed across classrooms and investigates instructional practices related to literary texts and functions of texts in instruction. The results reveal a strong genre discourse across classrooms; reading literary texts is strongly connected to students' own writing, focusing on generic text features that are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 51 publications
1
34
0
14
Order By: Relevance
“…Desse omgrepa har vunne stor hevd i arbeidet for å legitimere skjønnlitteraturens plass i skulen (f.eks. Andersen, 2011;Andersson, 2010;Gabrielsen et al, 2019). Nussbaum meiner at litteraturundervisning må bidraga til verdsborgarskap ved at vi «både føyer nye tekster til den velkjente vestlige litteraere 'kanon' og samtidig ser på standardtekstene med et veloverveid og kritisk blikk» (Nussbaum, 2016, s. 29).…”
Section: Kvalitet Og Representativitetunclassified
“…Desse omgrepa har vunne stor hevd i arbeidet for å legitimere skjønnlitteraturens plass i skulen (f.eks. Andersen, 2011;Andersson, 2010;Gabrielsen et al, 2019). Nussbaum meiner at litteraturundervisning må bidraga til verdsborgarskap ved at vi «både føyer nye tekster til den velkjente vestlige litteraere 'kanon' og samtidig ser på standardtekstene med et veloverveid og kritisk blikk» (Nussbaum, 2016, s. 29).…”
Section: Kvalitet Og Representativitetunclassified
“…Lipowski et al (2009) finner at dette omfatter positive og konstruktive tilbakemeldinger fra laereren og støttende og omsorgsfull laereratferd, både faglig og sosialt. Innenfor leseforskning viser en rekke studier (for eksempel Pressley, 2000;Guthrie, Klauda & Ho, 2013) at både laereres undervisning i lesestrategier og laereres stillasbygging er viktig for å utvikle elevenes leseforståelse, kunnskap om lesestrategier og leselyst.…”
Section: Beskrives Slikunclassified
“…OTL er et bredt begrep og inkluderer ofte laereplandekning, tid brukt på undervisning i faget og ressurser (Scheerens, 2016). Et viktig prinsipp i morsmålsundervisning er at elevene må eksponeres for mange ulike tekster og selv lese og skrive et mangfold av tekster (Gambrell, Malloy & Mazzoni, 2011;Graham et al, 2016). I norskfaget er det å eksponere elever for mange ulike teksttyper og tekstaktiviteter helt sentralt, både i laereplanene og i norskdidaktisk tradisjon.…”
Section: Beskrives Slikunclassified
See 1 more Smart Citation
“…A recent Norwegian study revealed that even though literature plays an important role in Language Arts education in school, little time is spent on students' own discussions on literature [1]. Most of the work related to literature consists of tasks about genre characteristics and detecting literary devices.…”
Section: Introductionmentioning
confidence: 99%